Transcriptional Activity of Baculovirus Very Late Factor 1 - Mistretta, Toni-Ann (American Society for Microbiology, 2005)
The product of the vlf-1 (very late factor 1) gene is required for expression of very late genes during the final phase of infection. To determine whether VLF-1 functions as a transcriptional activator, VLF-1 was overexpressed and purified by affinity and cation exchange chromatography. The addition of purified protein to transcription assays containing baculovirus RNA polymerase stimulated transcription of the very late polyhedrin promoter but not the late 39k promoter. Furthermore, construction and analysis of chimeric templates identified sequences within the polyhedrin promoter that were necessary for enhancement.